MANAJEMEN DIRI IBU HAMIL MASA PANDEMI COVID-19 DI DUSUN SUMBERAGUNG DESA SUMBERAGUNG KECAMATAN REJOTANGAN KABUPATEN TULUNGAGUNG - Muchsin, Enur (LPPM STIKes SATRIA BHAKTI NGANJUK, 2021)
The research objective was to determine self-management in pregnant women during the Covid-19 pandemic in Sumberagung Hamlet, Sumberagung Village, Rejotangan District, Tulungagung Regency. Descriptive research design, population of 30respondents with a sample of 30 respondents, sampling technique using total sampling, the study was conducted on Mei 8 to 20 , 2021, with a single variable self-management of pregnant women during the Covid-19 pandemic, questionnaire research instruments, data analysis using percentage formula and interpreted quantitatively. The results of the study were obtained from 30 respondents, almost all respondents had good self-management as many as 25 respondents (83,4%) and a small proportion of respondents had sufficient self-management as many as 5 respondents (16,6%). Self-management in pregnant women during the Covid-19 pandemic is influenced by factors of age, education, occupation, living together, gestational age, child pregnancy, and antenatal care